Deficiency of Calcitonin Gene-Related Peptide Affects Macrophage Polarization in Osseointegration - Yuan, Ying; Jiang, Yixuan; Wang, Bin; Guo, Yanjun; Gong, Ping; Xiang, Lin (Frontiers in Physiology, 2020)
Macrophage has been described as a critical cell population regulating bone regeneration and osseointegration, especially its polarization phenotype. Several studies have shown that calcitonin gene-related peptide-α (CGRP) might modulate macrophages polarization in inflammatory response and bone metabolism. This study aimed to investigate the effect of CGRP on macrophage polarization in titanium osseointegration. In vitro, bone marrow-derived macrophages (BMDMs) from C57BL/6 or CGRP-/- mice were obtained and activated for M1 and M2 polarization. Flow cytometry and real-time PCR were used to evaluate the M1/M2 polarization and inflammatory function. In vivo, mice were divided to 3 groups: wild-type, CGRP-/- and CGRP-/- mice with CGRP lentivirus. After extraction of the maxillary first molar, 0.6mm*1.25mm titanium implants were placed. Bone formation and inflammation levels around implants were then observed and analyzed. Results of flow cytometry demonstrated that CGRP deficiency promoted M1 polarization and inhibited M2 polarization in BMDMs, which were consistent with pro-inflammatory and anti-inflammatory cytokines expression levels in real-time PCR. In vivo, compared with CGRP-/- group, CGRP gene transfection group displayed better osseointegration and lower inflammation levels, which was close to wild-type group. These results revealed that CGRP might play roles in macrophage polarization. In addition, CGRP deficiency could inhibit the osseointegration in murine maxillae, while CGRP recovery by lentivirus transfection could improve osseointegration and regulate macrophage phenotype expression.